2017
DOI: 10.1038/leu.2017.151
|View full text |Cite
|
Sign up to set email alerts
|

Impact of killer-immunoglobulin-like receptor and human leukocyte antigen genotypes on the efficacy of immunotherapy in acute myeloid leukemia

Abstract: Interactions between killer-immunoglobulin-like receptors (KIRs) and their HLA class I ligands are instrumental in natural killer (NK) cell regulation and protect normal tissue from NK cell attack. Human KIR haplotypes comprise genes encoding mainly inhibitory receptors (KIR A) or activating and inhibitory receptors (KIR B). A substantial fraction of humans lack ligands for inhibitory KIRs (iKIRs), that is, a ‘missing ligand’ genotype. KIR B/x and missing ligand genotypes may thus give rise to potentially auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Elin Bernson has assessed the impacts of KIR/HLA genotypes in non-transplanted acute myeloid leukaemia. 13 The data showed that patients carrying the KIR B haplotype and/or with a 'missing ligand' genotype tended to have high natural cytotoxicity receptor expression and improved clinical outcome. In the session on infection, chaired by Becca Asquith, she presented mathematical modelling of host-virus dynamics and data from in vitro T-cell survival assays that support the hypothesis that inhibitory KIR, in the presence of their HLA class I ligands, enhance CD8 + T-cell control of three viral infectionshepatitis C virus, HIV and human T-lymphotrophic virus.…”
Section: Pregnancy Complications Cancer and Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elin Bernson has assessed the impacts of KIR/HLA genotypes in non-transplanted acute myeloid leukaemia. 13 The data showed that patients carrying the KIR B haplotype and/or with a 'missing ligand' genotype tended to have high natural cytotoxicity receptor expression and improved clinical outcome. In the session on infection, chaired by Becca Asquith, she presented mathematical modelling of host-virus dynamics and data from in vitro T-cell survival assays that support the hypothesis that inhibitory KIR, in the presence of their HLA class I ligands, enhance CD8 + T-cell control of three viral infectionshepatitis C virus, HIV and human T-lymphotrophic virus.…”
Section: Pregnancy Complications Cancer and Infectionmentioning
confidence: 99%
“…The data support the previously reported association of the Cen‐B haplotype motif with reduced relapse. Elin Bernson has assessed the impacts of KIR/HLA genotypes in non‐transplanted acute myeloid leukaemia . The data showed that patients carrying the KIR B haplotype and/or with a ‘missing ligand’ genotype tended to have high natural cytotoxicity receptor expression and improved clinical outcome.…”
Section: Pregnancy Complications Cancer and Infectionmentioning
confidence: 99%
“…KIR and KIR ligands were analyzed using the One Lambda KIR SSO Genotyping Test and the Olerup SSP KIR HLA Ligand kit, respectively, as described elsewhere (33). Patients were dichotomized based on concordance/discordance between their KIR and HLA genotypes.…”
Section: Kir/hla Genotyping and CMV Serologymentioning
confidence: 99%
“…Studies suggest that highly differentiated CMV-induced NK cells are important antileukemic effector cells in AML patients undergoing allo-SCT (4, 16,39). However, other studies propose that NS-iKIR NK cells might exert antineoplastic effector functions after immunomodulatory therapy (26,30,32,33). The high proportion of highly mature, adaptive NK cells along with the low proportion of NS-iKIR NK cells in CMV þ patients led us to examine the impact of CMV serostatus on clinical outcome.…”
Section: þ Serostatus Affects Negatively Outcome In Patients Recementioning
confidence: 99%
See 1 more Smart Citation